2021
DOI: 10.1017/s1368980021000975
|View full text |Cite
|
Sign up to set email alerts
|

Eating patterns in a nationwide sample of Japanese aged 1–79 years from MINNADE study: eating frequency, clock time for eating, time spent on eating and variability of eating patterns

Abstract: Objective: Although there is growing evidence suggesting that eating patterns are important determinants of health status, comprehensive information on patterning of eating behaviors is almost lacking. The aim of this cross-sectional study was to describe eating patterns in Japan. Design: Information on actual eating behaviors was collected using 2-d dietary record in each season over a year (total 8 d). Eating occasions were defined as any discrete intake occasion (with a discrete start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…In general, we found that the level of concordance between intake of Tier 1 food groups derived from the MDHQ and 4-day DR was similar across all meal types based on the median intake estimation and impressions from Bland–Altman analysis, but the ability to rank individuals according to intake level was higher for breakfast and snacks than for lunch and dinner. This finding may be due to the large between-person variability of food intake patterns at breakfast and snacks compared with that at lunch and dinner [ 6 , 19 , 32 ]. Alternatively, this may reflect the complex nature of lunch and dinner in terms of food consumption patterns compared with breakfast and snacks [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, we found that the level of concordance between intake of Tier 1 food groups derived from the MDHQ and 4-day DR was similar across all meal types based on the median intake estimation and impressions from Bland–Altman analysis, but the ability to rank individuals according to intake level was higher for breakfast and snacks than for lunch and dinner. This finding may be due to the large between-person variability of food intake patterns at breakfast and snacks compared with that at lunch and dinner [ 6 , 19 , 32 ]. Alternatively, this may reflect the complex nature of lunch and dinner in terms of food consumption patterns compared with breakfast and snacks [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study was based on the data collected from 14 (of the 47) prefectures between August and October 2021. Recruitment of participants and data collection were conducted by our research dietitians ( n = 66) with expertise in collecting DR data [ 18 , 19 ]. First, healthy women aged 30–69 years who were willing to participate and were living with their husbands were recruited for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a survey of breakfast, lunch, and dinner feeding habits was conducted among Japanese people. In that study, the time spent consuming breakfast, lunch, and dinner was 19, 25, and 34 min/d, respectively [ 46 ]. Thus, people who do not have enough time to serve meals, eat, and wash dishes in the morning may prefer Western-style breakfast, consume cereals and supplements, or skip breakfast.…”
Section: Discussionmentioning
confidence: 99%
“…The cereal breakfast-style group exhibited significantly quicker breakfast consumption than the other breakfast-style groups. A survey of breakfast was conducted among Japanese people, and the results demonstrated that feeding time clocks were longer—ranging from 5:00 to 10:00 (mean time, 7:24)—than lunchtime (range, 11:00–15:00, mean time, 12:29) [ 46 ], suggesting that people preferring breakfast at a later time may select Western and cereal breakfast types.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the survey procedure and participants have been described elsewhere [ 22 ]. In brief, a team of research dietitians with expertise in DR data collection ( n = 66) [ 23 , 24 ] collected data in 14 (of 47) prefectures from August to October 2021. For each prefecture, 8 community-dwelling couples, i.e., 2 women from each of the 4 age categories (30–39, 40–49, 50–59 and 60–69 years) and their husbands (irrespective of age), were recruited.…”
Section: Methodsmentioning
confidence: 99%